2022
DOI: 10.3390/ani12192566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Supplements on Growth Performance, Eating Behavior, Ruminal Fermentation, and Ruminal Morphology in Lambs during Transition from a Low- to a High-Grain Diet

Abstract: The objectives of this study were to investigate the effect of a maximum recommended oil supplementation on growth performance, eating behavior, ruminal fermentation, and ruminal morphological characteristics in growing lambs during transition from a low- to a high-grain diet. A total of 21 Afshari male lambs with an initial body weight (BW) of 41.4 ± 9.1 kg (mean ± SD) and at 5–6 months of age were randomly assigned to one of three dietary treatments (n = 7 per group), including (1) a grain-based diet with no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although limited documents are available on the effect of supplemental lipid on oxidative stress indicators in dairy calves [ 48 ], Tsai et al [ 49 ] indicated that SBO rich in linoleic acid has some pro-inflammatory effect in young ruminants that can modulate intake and performance in pre-weaning calves. The ruminal metabolism of FA should also be considered with caution when lipid supplementation is provided to dairy cows [ 50 , 51 ], calves [ 52 ] or lambs [ 14 , 15 ]. Most of the negative responses to supplemental unsaturated FA had been attributed to its negative influence on ruminal fermentation and microbial activity in calves under 2 months of age [ 13 , 46 ]; however, it seems that additional effects on energy metabolism and its hormonal regulation, as well as on oxidative stress and possibly inflammation, should receive additional attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although limited documents are available on the effect of supplemental lipid on oxidative stress indicators in dairy calves [ 48 ], Tsai et al [ 49 ] indicated that SBO rich in linoleic acid has some pro-inflammatory effect in young ruminants that can modulate intake and performance in pre-weaning calves. The ruminal metabolism of FA should also be considered with caution when lipid supplementation is provided to dairy cows [ 50 , 51 ], calves [ 52 ] or lambs [ 14 , 15 ]. Most of the negative responses to supplemental unsaturated FA had been attributed to its negative influence on ruminal fermentation and microbial activity in calves under 2 months of age [ 13 , 46 ]; however, it seems that additional effects on energy metabolism and its hormonal regulation, as well as on oxidative stress and possibly inflammation, should receive additional attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies addressed the interaction effect of forage source and lipid supplement on performance of dairy calves [ 11 , 13 ]; however, the combined effects of forage particle size and lipid supplement need to be evaluated in dairy calves. In addition, as stated in previous studies [ 12 , 14 , 16 ], lipid supplement may have different impacts from the oxidative stress perspective, which can eventually influence whole animal body metabolism. The interactive effect of FPS with different lipid supplement on the oxidative stress of young calves also needs to be evaluated in dairy calves.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation